(untitled) (Research, Society and Development, 2021)
Long-stay institutions are a source of support for a large number of elderly people, aiming to maintain the functional capacity of these oldest-olds, being a great challenge, since institutionalization sometimes represents an unfavorable outcome for them. The objective of the research is to identify the impacts of institutionalization on the functional capacity of the elderly in a Long-Term Institution. Ethical precepts were respected (Res. CNS 466/12) and care was maintained in the face of the COVID-19 pandemic. The study is observational, cross-sectional, descriptive, with a quantitative approach carried out with 30 elderly residents of the ILPI. The present research showed that 43.33% of the elderly studied are functionally independent in the Kartz index score. It is noteworthy that the majority were male (93.33%), aged between 60 and 69 years; 76.68% of the evaluated elderly were illiterate. Institutionalized elderly have greater difficulties in activities related to personal hygiene, and less difficulties in feeding practices and transference. Income also alters the living dynamics of institutionalized individuals and chronic diseases present themselves as limiting factors. This study evidenced important impacts of institutionalization on the functional capacity of the elderly, demonstrating that maintaining the integrity and independence of the oldest old is an important challenge.